Temperature self-regulating flat electric heaters based on MWCNTs-modified polymers; Polymer Bulletin; Vol. XX - Ali I. Imran; AlGharni T. S. Tahani Saad; Shchegolkov A. Alexandr; Shchegolkov A. Aleksei; Jang Sung-Hwan; Galunin E. V. Evgeny Valerjevich; Komarov F. Fadey; Borovskikh P. Pavel; Imanova G. T. Gunel (2020, 2020)
Title screen